Penerapan Pembelajaran Google Classroom Berbantuan Video Animasi terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri 5 Pekalongan - Fathimatuz Zahra An-Nawaf; Sayyidatul Karimah; Syita Fatih ‘Adna (Journal of Instructional Mathematics, 2021)
Distance learning aims to break the spread of Covid-19 in Indonesian. Learning media is needed to deliver the material so that mathematical problem solving (MPS) abilities are better. This study aims: (1) to monitor the MPS abilities of students who used Google Classroom in SMP Negeri 5 Pekalongan with the help of animated videos to achieved KKM; (2) to found out the MPS abilities of students who used Google Classroom with the help of animated videos, it was better than those who used WhatsApp Group (WAG) with assignments. This type of research was a Posttest-Only Control Design. The research sample was taken through the cluster random sampling technique from all students of eight graders in SMP Negeri 5 Pekalongan. Data collection techniques were obtained through tests. Data analysis used the proportion test to determining student learning completeness and the mean difference test (test) to determine the difference in the mean between the two groups. The results of this study: (1) students’ MPS abilities used Google Classroom with the help of animated videos to achieved KKM; (2) students’ MPS abilities used Google Classroom with the help of animated videos, it was better than those who used WAG with assignments.